1983
DOI: 10.1126/science.6823561
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Parkinsonism in Humans Due to a Product of Meperidine-Analog Synthesis

Abstract: Four persons developed marked parkinsonism after using an illicit drug intravenously. Analysis of the substance injected by two of these patients revealed primarily 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine (MPTP) with trace amounts of 1-methyl-4-phenyl-4-propionoxy-piperidine (MPPP). On the basis of the striking parkinsonian features observed in our patients, and additional pathological data from one previously reported case, it is proposed that this chemical selectively damages cells in the substantia nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
1,893
1
43

Year Published

1986
1986
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,500 publications
(1,954 citation statements)
references
References 3 publications
17
1,893
1
43
Order By: Relevance
“…The interest in the relationship between pesticides and PD was raised in the 1980s, when it was discovered that exposure to 1-methyl-4-phenyl-1, 2, 3, 6,-tetrahydropyridine (MPTP), a substance structurally similar to the herbicide paraquat, resulted in chronic parkinsonism and degeneration of dopaminergic neurons in humans [281]. An ecological study reported high prevalence of PD in rural agricultural regions in Canada [282].…”
Section: Pesticidesmentioning
confidence: 99%
“…The interest in the relationship between pesticides and PD was raised in the 1980s, when it was discovered that exposure to 1-methyl-4-phenyl-1, 2, 3, 6,-tetrahydropyridine (MPTP), a substance structurally similar to the herbicide paraquat, resulted in chronic parkinsonism and degeneration of dopaminergic neurons in humans [281]. An ecological study reported high prevalence of PD in rural agricultural regions in Canada [282].…”
Section: Pesticidesmentioning
confidence: 99%
“…The dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [MPTP] is known to induce parkinsonism in hu-mans, primates, and mice ( [27,90,132,133]). MPTP is converted by astrocytes to the metabolite 1 methyl-4-phenylpyridinium [MPP + ], a substrate of the DA transporter ( [40,41]).…”
Section: Animal Models Of Parkinson's Diseasementioning
confidence: 99%
“…Administration of MPTP to man or non-human primates (Davis et al 1979;Langston et al 1983;Burns et al 1983) including common marmosets (Jenner et al 1984) induces a selective destruction of dopaminergic nigrostriatal neurons associated with a substantial decrease in dopamine content of the caudate nucleus and putamen. MPTP is converted by monoamine oxidase type B (MAO-B) into the dihydropyridinium species (MPDP ÷) which is converted non-enzymatically into the neurotoxic l-methyl-4-phenylpyridinium ion (MPP ÷; Castagnoli et al 1985).…”
Section: Introductionmentioning
confidence: 99%